Pemetaan Daerah Resapan Air di Kota Padang - Andarizma, Chandra (JURNAL BUANA, 2025)
The city of Padang is currently experiencing developments in housing and settlement development. These activities cause changes in land use which results in the soil surface being impermeable to water. The soil surface is impermeable to water, it can inhibit the infiltration process. In addition, the city of Padang has a high risk of flooding. This has the impact of causing a flood disaster in the city of Padang. The purpose of this study, among others, is to determine the infiltration ability of Padang City and the distribution of water absorption conditions in Padang City. Analysis of the data used include: scoring, overlay and descriptive analysis. Infiltration capability in Padang City is divided into five classes and is dominated by moderate infiltration. The water catchment conditions in Padang City are divided into six classes and are dominated by good conditions.